Fiqh Analysis of Four Schools Against the Mappatabe' Tradition in South Sulawesi - Abu Haif; Arwinni Eka Putri Ahmad; Panji Anugrah; Muhammad Afif; Ahmad Muhajir Almusafir; Ismail Ismail; Hasna Mardanus; Zulfitriana Zulfitriana; Abd. Rahman (Universitas Islam Negeri Sumatera Utara, 2026)
Islamic civilization has developed dynamically and continuously interacted with local cultures through a selective process of acculturation. In Indonesia, particularly in South Sulawesi, the tradition of mappatabe'-which involves saying “tabe'” while slightly bowing as a sign of respect toward elders-represents a clear example of the integration between local culture and Islamic values. Nevertheless, this practice has generated fiqh-related debates concerning the limits of human respect so that it does not resemble acts of worship such as rukūʿ or sujūd, which are exclusively devoted to Allah SWT. This study aims to examine and analyze the perspectives of the four Sunni schools of Islamic jurisprudence Hanafi, Maliki, Shafi‘i, and Hanbali) regarding the mappatabe' tradition as a local cultural practice within the framework of Islamic law. The research employs a library-based qualitative method with a normative-fiqh approach, supported by ex post facto and descriptive methods to explore causal relations and to describe the practice of mappatabe' in its social and legal contexts. Data were collected from primary sources, including the Qur'an, the Prophet's hadiths, classical fiqh texts of the four schools, works of contemporary scholars, and relevant religious fatwas, complemented by secondary sources such as academic books and scholarly journal articles. The findings indicate that the mappatabe' tradition is fundamentally permissible as long as it is understood as a form of social etiquette and respect, does not involve elements of servitude or worship, does not resemble the physical acts of rukuʿ or sujud, and does not promote discrimination among individuals. Therefore, mappatabe' can be regarded as a form of cultural acculturation that aligns with the principles of Islamic law and reflects noble moral values in social life.